Answer:
1) Repaid for the loan = $239,511.60
2) Percentage = 58.2%
3) Average amount = $387.53
Step-by-step explanation:
Given :
Amount $100,000
Rate 7%
Payments 360 - $665.31
Total interest $139,511.60
To find :
1) How much will be repaid for this loan?
Repaid for the loan = Amount - Total interest
Repaid for the loan = 100,000 + 139,511.60
Repaid for the loan = $239,511.60
2) What percentage will be repaid for this loan?
![\text{Percentage}=\frac{\text{Total interest}}{\text{Repaid loan}}\times100](https://tex.z-dn.net/?f=%5Ctext%7BPercentage%7D%3D%5Cfrac%7B%5Ctext%7BTotal%20interest%7D%7D%7B%5Ctext%7BRepaid%20loan%7D%7D%5Ctimes100)
![\text{Percentage}=\frac{139511.60}{239511.60}\times100](https://tex.z-dn.net/?f=%5Ctext%7BPercentage%7D%3D%5Cfrac%7B139511.60%7D%7B239511.60%7D%5Ctimes100)
![\text{Percentage}=0.582\times100](https://tex.z-dn.net/?f=%5Ctext%7BPercentage%7D%3D0.582%5Ctimes100)
![\text{Percentage}=58.2\%](https://tex.z-dn.net/?f=%5Ctext%7BPercentage%7D%3D58.2%5C%25)
3) What will be the average amount per payment for interest?
![\text{Average amount}=\frac{\text{Total interest}}{\text{Payments}}](https://tex.z-dn.net/?f=%5Ctext%7BAverage%20amount%7D%3D%5Cfrac%7B%5Ctext%7BTotal%20interest%7D%7D%7B%5Ctext%7BPayments%7D%7D)
![\text{Average amount}=\frac{\text{139511.60}}{\text{360}}](https://tex.z-dn.net/?f=%5Ctext%7BAverage%20amount%7D%3D%5Cfrac%7B%5Ctext%7B139511.60%7D%7D%7B%5Ctext%7B360%7D%7D)
![\text{Average amount}=387.53](https://tex.z-dn.net/?f=%5Ctext%7BAverage%20amount%7D%3D387.53)
ANSWER
See below
EXPLANATION
Given
![f(x) = \frac{ {x}- 9 }{x + 5}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%5Cfrac%7B%20%7Bx%7D-%209%20%7D%7Bx%20%2B%205%7D%20)
and
![g(x) = \frac{ - 5x - 9}{x - 1}](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%20%20%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%20)
![(f \circ \: g)(x)= \frac{ (\frac{ - 5x - 9}{x - 1})- 9 }{(\frac{ - 5x - 9}{x - 1} )+ 5}](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%28%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%29-%209%20%7D%7B%28%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%20%29%2B%205%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9 - 9(x - 1)}{x - 1}}{\frac{ - 5x - 9 + 5(x - 1)}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209%20-%209%28x%20-%201%29%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20-%209%20%2B%205%28x%20-%201%29%7D%7Bx%20-%201%7D%20%7D%20)
Expand:
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9 - 9x + 9}{x - 1}}{\frac{ - 5x - 9 + 5x - 5}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209%20-%209x%20%20%2B%209%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20-%209%20%2B%205x%20-%205%7D%7Bx%20-%201%7D%20%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9x + 9 - 9}{x - 1}}{\frac{ - 5x + 5x - 5 - 9}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209x%20%20%2B%209%20-%209%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20%2B%205x%20-%205%20-%209%7D%7Bx%20-%201%7D%20%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 14x }{x - 1}}{\frac{ -14}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%2014x%20%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-14%7D%7Bx%20-%201%7D%20%7D%20)
Since the denominators are the same, they will cancel out,
![(f \circ \: g)(x)= \frac{ - 14x}{ - 14} = x](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%5Cfrac%7B%20-%2014x%7D%7B%20-%2014%7D%20%20%3D%20x)
A={2,3,5}
B={1,3,4}
A∩B={3}
R: a. {3}
1. 7 hours and 40 min
2. 1 hour and 24 min
3. 4 hours and 45 min
4. 8 hours and 48 min
Answer:
41/168
Step-by-step explanation:
100% sure jus did it